2019
DOI: 10.1021/acs.jpcc.9b08018
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Nucleobases on Doped MoS2 Monolayer: A DFT Study

Abstract: Nucleobases detection is important in DNA sequencing, disease testing linked to genes, and disease treatment. In this work, the interactions of nonmetallic element (Si, P, Cl, Se) doped MoS2 monolayer and nucleobases (A, C, G, T, U) have been studied by first-principles based on density functional theory. Their optimal configurations, the corresponding adsorption energies, charge transfer, and electrical properties are calculated. The adsorption strength and charge transfers after doping Si and P are all large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The preferable adsorption site of the Au and Li atoms on silicene and germanene monolayers is a hollow site, see M. Sadeghi et al [25] showed that the Li atom can improve the binding energy between the nucleobases and, MoS 2 . Song et al [50] showed that the Au atom can increase the binding energy between the aromatic amino acids such as phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp) on MoS 2 monolayer. Additionally, Gorkan et al [17] and Kadioglu et al [51] reported that interactions of amino acids and nucleobases with Au clusters supported blue and black phosphorene, respectively.…”
Section: Binding Mechanism Of Li/au-doped Silicene and Germanene Monomentioning
confidence: 99%
“…The preferable adsorption site of the Au and Li atoms on silicene and germanene monolayers is a hollow site, see M. Sadeghi et al [25] showed that the Li atom can improve the binding energy between the nucleobases and, MoS 2 . Song et al [50] showed that the Au atom can increase the binding energy between the aromatic amino acids such as phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp) on MoS 2 monolayer. Additionally, Gorkan et al [17] and Kadioglu et al [51] reported that interactions of amino acids and nucleobases with Au clusters supported blue and black phosphorene, respectively.…”
Section: Binding Mechanism Of Li/au-doped Silicene and Germanene Monomentioning
confidence: 99%
“…Clearly, nucleobases on both sides of the 1H–MoOS monolayer energetically adopt a parallel orientation. Related to the adsorption of nucleobases on the Janus MoOS Mo–O side (Mo–S side), the order of adsorption energies is G > A > C > T > U, which is very similar to those of 2D pristine MoS 2 [ 45 , 46 , 47 ]. The adsorption energies of A, C, T, and U on the O layer (S layer) are −0.86 (−0.89), −0.81 (−0.82), −0.71 (−0.76), and −0.64 (−0.67) eV, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, by exploring the energy decomposition (see Table 1 and Table 2 ), the binding energy is split into destabilized (positive) and minor deformation energies related to G, A, C, T, and U adsorption states, respectively, and stabilized (negative) with predominant interaction energies between nucleobases with oxygen and sulfur layer sides of the Janus MoOS surfaces (vdW interactions). In addition, the reason that G exhibits the largest binding energy or smallest interaction energy in both sides (O layer or S layer) of the Janus MoOS monolayer and other biomaterials [ 7 , 18 , 45 , 48 , 49 , 50 , 51 , 52 ], is relatively associated with high polarizability prior to other nucleobases [ 50 , 52 , 53 ]. This trend is more encouraging by the charge density distributions and molecular interactions (in the supplementary materials see Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is recommended to use radiation to speed up drug desorption. 62 It has been well established that in the treatment of cancer, ultrasonic waves that have been used in conjunction with chemotherapy increase the temperature of cancer tissue to 42–45 °C. 63 Accordingly, we have considered the frequency of the ultrasonic wave ( ν 0 = 2 × 10 4 s −1 ) as the attempted frequency for calculations of the recovery time.…”
Section: Resultsmentioning
confidence: 99%